Samhällstjänsten som ett självdisciplinerande straff - Henrik Linderborg (Nordisk Tidsskrift for Kriminalvidenskab)
This article presents findings from an interview study of 28 persons serving sentences of community service. The interviews were conducted during the spring of 1999. Subjects reported believing that successful completion of their community service - which often lasted several months - required them to assume more responsibility for their own lives. The average length of time served doing community service was 140 hours. The sentence was usually served twice a week, four hours at a time. Depending on a person’s life circumstances, community service was performed either on weekends or during the evenings after working hours. Unemployed persons doing community service served their time during the day. All of those interviewed thought that community service, when performed in this way, required that they be able to plan their everyday lives in the long-term. This was by no means easy for all of them. Most of those interviewed had been, or still were, drinkers or drug users, and therefore remained involved in a kind of lifestyle that diverged in many ways from the conventional lifestyle based on paid work. The long-term planning and regularity demanded by community service required many of those interviewed to force themselves to behave, for example, by not drinking, so as not to spoil their chances of completing their punishment.